Institutionalizing Monitoring and Evaluation Systems : Five Experiences from Latin America - Burdescu, Ruxandra; del Villar, Azul; Mackay, Keith; Rojas, Fernando; Saavedra, Jaime (World Bank, Washington, DC, 2012)
Many governments in the Latin America and Caribbean region (LAC) have gained an increased understanding of the value of M&E to help both governments and donors alike better understand what public investments and interventions work well, which do not, and the reasons why. Monitoring the performance of public programs and institutions helps increase their effectiveness, provides increased accountability and transparency in how public monies are used, and can inform the budgetary process and the allocation of public resources, thus improving their effectiveness to improve welfare and, consequently, reduce poverty and increase the equality of opportunities.